Testing the applicability of a model of oral health-related quality of life - Camila Mello dos Santos; Roger Keller Celeste; Juliana Balbinot Hilgert; Fernando Neves Hugo (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
The aim of this study was to test Wilson & Cleary's conceptual model of the direct and mediated pathways between clinical and non-clinical variables in relation to oral health-related quality of life. A random sample of 578 older people was evaluated. Wilson & Cleary's conceptual model was tested using structural equations modeling including: biological variables, symptom status, functional health, oral health perceptions, oral health-related quality of life. Oral health-related quality of life was assessed with the Oral Health Impact Profile-14 (OHIP-14). In the final model, edentulism was negatively correlated to dissatisfaction of appearance of their dental prostheses (r = -0.25). Worse functional status was correlated with poor oral health perception (r = 0.24). Being aged over 68 (r = 0.25), being a female (r = 0.39) and living in rural areas (r = 0.15) had a direct effect on the edentulism. Age had a direct effect on OHIP-14 (r = -0.15). There was an indirect effect of sex on OHIP-14 via functional status (r = 0.12). The present findings partially support Wilson & Cleary's model framework.